2021
DOI: 10.51622/jispol.v1i2.418
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Strategi Pemasaran Terhadap Peningkatan Volume Penjualan Lahan Di Pt. Kawasan Industri Modern (Persero) Medan

Abstract: This study aims to determine the effect of marketing strategies, namely pricing strategies and promotional costs carried out by PT. Kawasan Industri Modern  (Persero) to increase the volume of land sales. The method used is a quantitative method. This study uses secondary data types and the data analysis used is multiple regression data analysis, partial regression analysis and equipped with classical assumption test. The results of the regression analysis show that partially the pricing strategy has a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…The price set by producers for a product depends on t he amount of demand for that product. If there is much demand, but few products are available, the price offered is relatively high (Sianturi & Simanjuntak, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The price set by producers for a product depends on t he amount of demand for that product. If there is much demand, but few products are available, the price offered is relatively high (Sianturi & Simanjuntak, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Research is carried out for the sake of obtaining scientific facts. In order to obtain these facts, a method is needed in research (Sianturi, C. &;Simanjuntak, J.M., 2021). In research, there are at least two methods that are most often used in research are qualitative and quantitative methods.…”
Section: Methodsmentioning
confidence: 99%
“…The use of these analytical techniques aims to analyze and process data, so that it can be concluded that independent variables (promotion and sales strategies) affect the dependent variable (number of sales). The equation for multiple linear regression is as follows: According to Sianturi (2021), this t test is applied as an evaluation of how each independent variable, namely between promotion strategy (X1) and sales (X2), affects the dependent variable, namely the number of sales (Y) at a confidence level of 5% (0.05). Therefore, the criteria for decision making can be described as follows: 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations